Distribution and encounter rates of the river dolphin (Inia geoffrensis boliviensis) in the central Bolivian Amazon - Aliaga-Rossel, E.; McGuire, T. L.; Hamilton, H. (J. Cetacean Res. Manage., 2023)
The ecology and conservation status of river dolphins (Inia sp.) distributed in the lowland rivers of Bolivia are poorly understood and only recently have basic studies been conducted to investigate their population size, taxonomic status, distribution, behaviour, environmental threats and ecology in this region. This paper examines the distribution and encounter rates of the bufeo (Inia sp.) in the middle reach of the Bolivian Amazon and was conducted in the Mamoré River and four of its tributaries during the low water season. Methods were employed which can be replicated during future surveys of Bolivian river dolphins and the results can be compared with those from surveys of Inia throughout its range. Sixty-two hours were spent surveying for dolphins, with 68% of the effort in Mamoré River and 32% in its tributaries. The Inia encounter rates reported here (1.6-5.8 dolphins km21) are the highest recorded anywhere in its broad geographic range; and indicate the importance of continuing and expanding surveys in this area. The mean group size was greatest in the Tijamuchi River (3.3±2.96) and smallest in the Yacuma River (1.8±0.75) and the maximum group size was 14. The high bufeo encounter rates in the central Bolivian Amazon can be taken as a reflection of the general environmental status of the region; however, a growing human population, associated with an increase in boat traffic and fishing activity, poses a future threat to bufeos and their aquatic habitats.